SPOKEN HISTORIES OF DISPLACED SERBS FROM KOSOVO AND METOHIJA: INFLUENCE OF FORCED MIGRATIONS ON THE CONCEPT OF HOME (Heritage, 2021)
Displacement of Serbs from Kosovo and Metohija at the end of the nineties was influenced by the armed conflict between paramilitary forces of Kosovo Liberation Army on one side, and Serbian police forces and military forces of the Federal Republic of Yugoslavia on the other. This conflict was the root cause of NATO aggression against the Federal Republic of Yugoslavia that led to the forced migration of more than 200.000 Serbs and non-Albanians from Kosovo and Metohija.This article entails analysis of the spoken histories of displaced Serbs from Kosovo and Metohiјa, as well as of secondary sources that form part of family folklore of their loss. These secondary sources are the personal stories of members of displaced families who do not have direct memories of displacement from and life in Kosovo and Metohija, or who left Kosovo and Metohija in the early stages of their lives. Analyses of these primary and secondary sources have led to identification of structural factors that have influenced the construction of home as a category which has been shaped by symbolical maps created by displacement. It has been shown that displacement constructs place identities which are tied to forcefully abandoned places.
Keywords: home, spoken histories, internaly displaces presons, Serbs, Kosovo and Metohija, place identity.